(untitled) (Patan Pragya, 2019)
Intimate Partner Violence (IPV) is a major public health phenomenon. The objective of this study is to explore the prevalence and associated risk factors of intimate partner violence in Kathmandu valley. For this study, the data had come from Nepal Demographic and Health Survey (NDHS), 2016. Study has confined 162 married women from three districts of Kathmandu valley. Bivariate analysis and logistic regression were applied to examine the association between variables. Results found that more than a quarter (27%) women had faced at least one form of violence and education is significant variable for both women and husbands. Therefore, national attention should stand towards education for both women and their husbands to mitigate IPV.